Mechanism underlying NMDA blockade-induced inhibition of aggression in post-weaning socially isolated mice. (December 2018) - Chang, Chih-Hua; Su, Chun-Lin; Gean, Po-Wu
Abstract: When faced with stressful conditions, people with a tendency toward impulsive aggression may suddenly hurt others. We have previously shown that the blockade of NMDA receptors (NMDARs) within the ventral hippocampus (VH) produces anti-aggressive effects. However, little is known about the mechanism for tamping down stress-provoked attack behavior. Here, we report that expression of brain-derived neurotrophic factor (BDNF) after inhibition of NMDARs in the VH is required for blunting stress-provoked attack behavior in post-weaning socially isolated mice. Administration of NMDAR antagonist MK-801 decreased the phosphorylated eukaryotic elongation factor 2 (p-eEF2) and increased BDNF expression in the VH. Infusion of eEF2 kinase inhibitor NH125 to the VH decreased attack behavior and increased BDNF expression. Knockdown of BDNF in the VH blocked the anti-aggressive effect of MK-801 and NH125. Furthermore, MK-801 rapidly increased the activity of protein phosphatase 2A (PP2A). Intra-VH infusion of PP2A inhibitor okadaic acid blocked the anti-aggressive effects of MK-801. These results suggest that blockade of NMDAR reduces attack behavior through increasing PP2A activity leading to dephosphorylation of eEF2 and an increase in BDNF expression. Our findings indicate that the enhancement of BDNF expression is beneficial for preventing impulsive aggression in at-risk beings. Graphical abstract: Highlights: Acute stress exaggerates attack behavior in post-weaning socially isolated mice. NMDA blockade, MK-801, decreases attack behavior via eEF2-BDNF signaling. MK-801 rapidly increases the activity of protein phosphatase 2A. Protein phosphatase 2A, but not mTOR, mediates MK-801-induced BDNF expression.